Respuesta :

[|] Answer [|]

[tex]\boxed{N \ = \ 7/10}[/tex]

[|] Explanation [|]

(2n + 4) + 6 = -9 + 4(2n + 1)

N = ?

____________

Expand: - (2n + 4) + 6:     -2n + 2

- (2n + 4)     -2n - 4

= -2n - 4 + 6

Add / Subtract Numbers: -4 + 6 = 2

= -2n + 2

Expand: -9 + 4(2n + 1):   8n - 5

-9 + 4 (2n = 1)

Expand: 4(2n + 1):   8n + 4

= -9 + 8n + 4

Add / Subtract Numbers: -9 + 5 = -5

= 8n - 5

_________________

-2n + 2 = 8n - 5

Subtract 2 From Both Sides:

-2n + 2 - 2 = 8n - 5 - 2

Simplify:

-2n = 8n - 7

Subtract 8n From Both Sides:

-2n - 8n = 8n - 7 - 8n

Simplify:

-10 = -7

Divide Both Sides By -10:

-10/-10 = -7/-10

Simplify:

N = 7/10

[tex]\boxed{[|] \ Eclipsed \ [|]}[/tex]

ACCESS MORE